Optimalisasi Mutu Pendidikan Melalui Manajemen Berbasis Sekolah (MBS) - Cindy Rahma Eka W; Saudah Khodijah; Aprilia Kinantika sari; Dinda Permatasari; Yohanes Anando Aryo; Maria Melani Ika Susanti (Jurnal Pendidikan, Sains Dan Teknologi, 2025)
Education plays an important role in determining the progress of a nation. However, in Indonesia, the quality of education still faces quite complex challenges. Some of the main problems that arise in the education sector include the low professionalism of some teachers, limited facilities and infrastructure to support learning, and minimal involvement of related parties in supporting the education process as a whole. This study aims to examine the implementation of School-Based Management (SBM) as one of the strategic approaches in efforts to improve the quality of education, especially at the elementary school level. This study uses a qualitative method with a descriptive approach, and relies on literature studies and case studies related to elementary education. Data were analyzed through data reduction analysis techniques, data presentation, and drawing conclusions. Researchers identified patterns, themes, and relationships between the implementation of SBM and improving the quality of education in various previous studies. The results of the study indicate that the implementation of School-Based Management is able to increase the effectiveness of education management by involving all elements in the school environment. Principals, teachers, students, parents, school committees, and the community actively participate in the planning, implementation, and evaluation stages of the program. The collaboration formed through this approach fosters a sense of shared responsibility and creates a democratic learning atmosphere. Thus, MBS has proven to be able to strengthen school independence, encourage increased institutional capacity, and create a higher quality learning process.